Publications relating to the reactions of medical students to human cadavers and ethics - Karatas, Mehmet (Acta Bioethica, 2018)
Objectives: Faculty of Medicine students are practicing on a human cadaver in the course of education especially in Anatomy lessons. There are some physical, emotional, and ethical problems that students have experienced with participation in these lessons. In some publications we have reviewed issues regarding these, we aimed to reveal whether ethical issues are being addressed. Methods: We conducted literature searches by writing the clues “Publications relating to the Faculty of Medicine student’s reactions to cadavers lessons and ethics” on search engines on the internet. By examining the articles obtained, we investigated whether students are experiencing problems, especially on ethics. Results: 28 articles (90.3%) were original research, 2 (6.4%) were reviews and 1 (3.2%) was a book. Only 6 out of these studies (19.3%) have addressed ethical issues. In our research, quite a few publications (19.3%) have been found that dealt with ethical problems in cadaver lessons. Human body dissection during an anatomy course for the first-year medical students raises questions about invasion of privacy, cadaver sources, dying, and death. Conclusion: Detailed reviews of the situations that causes ethical problems in the studies to be done in this direction are thought to be beneficial to the medical faculties students education.